2006 Fortieth Asilomar Conference on Signals, Systems and Computers 2006
DOI: 10.1109/acssc.2006.356588
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Floating-Point to Fixed-Point Transformations

Abstract: Abstract-Many digital signal processing and communication algorithms are first simulated using floating-point arithmetic and later transformed into fixed-point arithmetic to reduce implementation complexity. For the floating-point to fixed-point transformation, this paper describes two methods within an automated transformation environment. The first method, a gradientbased search for single-objective optimization with sensitivity information, provides a single solution, and can become trapped in local optima.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…First, we have computed the coefficients of several low-pass and high-pass FIR filters for different number of taps using Matlab. Then, the floating-point version of the filters, considering the direct-form structure, has been optimized for fixed-point computation using "FloatingPoint to Fixed-Point Transformation Toolbox" [7]. For a given error threshold, this Matlab toolbox optimizes the worth-length combination of the given DSP data-path to minimize the estimated area cost of the circuit when implemented it on FPGA.…”
Section: Results and Comparisonmentioning
confidence: 99%
“…First, we have computed the coefficients of several low-pass and high-pass FIR filters for different number of taps using Matlab. Then, the floating-point version of the filters, considering the direct-form structure, has been optimized for fixed-point computation using "FloatingPoint to Fixed-Point Transformation Toolbox" [7]. For a given error threshold, this Matlab toolbox optimizes the worth-length combination of the given DSP data-path to minimize the estimated area cost of the circuit when implemented it on FPGA.…”
Section: Results and Comparisonmentioning
confidence: 99%
“…The linear fitting method is introduced in reference [12] to implement the Logarithmic 2 module. It divides (1,2] span into 128 segments, while each segment corresponds to a slope and a bias. Computation begins with shifting input to (1,2] span, then the section is chosen correspondingly to get the result.…”
Section: A a Look-up Table Methods On Logarithm 1) Arithmetic Descripmentioning
confidence: 99%
“…According to extreme value theory, maximum and minimum are converged to Gumbel distribution. Maximum is got by (2).…”
Section: ) Extreme Value Theory Approachmentioning
confidence: 99%
“…However, this work was limited to monoobjective optimization only. More recently, Han et al [49] reported EA-based multiobjective wordlength optimization for a filtering application. This work, however, considered only linear objective functions and lacked postsynthesis validation.…”
Section: Discussionmentioning
confidence: 99%